Kaempferia parviflora Wall. ex Baker (Zingiberaceae) - A new record for Bangladesh - Yusuf, Mohammed; Begum, Jaripa (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(2): 89-92, 2003 (December)